2021
DOI: 10.3390/nu13062118
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High Triglycerides Level in Predicting Cognitive Impairment: A Review of Current Evidence

Abstract: The burden of cognitive disorders is huge and still growing, however the etiology and the degree of cognitive impairment vary considerably. Neurodegenerative and vascular mechanisms were most frequently assessed in patients with dementia. Recent studies have shown the possible involvement of triglycerides levels in cognitive function through putative mechanisms such as brain blood barrier dysfunction or amyloid metabolism imbalance, but not all research in the field found this association. Several clinical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Triglycerides are lipids that store and transport energy in the body. High levels of triglycerides are generally associated with increased risk of cognitive impairment over time ( 31 ) and non-Alzheimer's dementia ( 32 ), although evidence is sparse and non-associations have also been reported ( 31 , 33 ). A few cross-sectional studies have reported similar results to ours, where low levels of triglycerides were associated with dementia ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Triglycerides are lipids that store and transport energy in the body. High levels of triglycerides are generally associated with increased risk of cognitive impairment over time ( 31 ) and non-Alzheimer's dementia ( 32 ), although evidence is sparse and non-associations have also been reported ( 31 , 33 ). A few cross-sectional studies have reported similar results to ours, where low levels of triglycerides were associated with dementia ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, altered BA profiles may reflectimbalances in lipid metabolism during METH withdrawal. Hyperlipidemia, especiallyexcess TGs, has been reported to affect the development of neural cognition and mooddisorders through putative mechanisms such as brain blood barrier dysfunction or animbalance in amyloid metabolism ( 45 47 ). The present studyshowed that the plasma concentrations of TGs and LDL-cholesterol correlatedpositively with both HAM-A and HAM-D scores, whereas the plasma concentrations ofHDL-cholesterol correlated negatively with HAM-D scores.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a rapid and direct way of modifying the gut microbiota composition and function, reducing inflammation, and helping in eubiosis maintenance [ 123 , 164 , 165 ]. Given the evidence of association between neuropsychiatric conditions and gut microbiota dysregulation, it is worth speculating that dietary interventions could represent effective candidates for preventing and delaying the pathogenesis and progression of AD [ 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ] ( Table 2 ). Here, we present some of the most promising dietary therapies proposed in the literature, with a particular focus on Mediterranean and ketogenic diets.…”
Section: Mainmentioning
confidence: 99%
“…Overall, lipid dysregulation might contribute to AD pathogenesis, enhancing synaptic loss, BBB dysfunction, mitochondrial disruption, oxidative stress, and inflammation [ 198 , 205 ]. Indeed, in large longitudinal studies, high levels of triglycerides and cholesterol in the serum are significantly associated with cognitive impairment [ 178 ]. Again, a recent cross-sectional study with 689 participants including AD and healthy patients, revealed that reduced levels of triglycerides were related to better cognitive performance and a reduction in brain dysfunction and atrophy [ 206 ].…”
Section: Mainmentioning
confidence: 99%